Determination of Some Mineral Salts and sugar concentration of orange and lemon varieties (Journal of Humanitarian and Applied Sciences, 2017)
This study included the evaluation of some mineral salts such as sodium and potassium for different varieties of oranges and lemons obtained from the local market of the city of Al-khums. The study was included samples of oranges and lemon (blood orange, sour orange, navel orange, mandarin Orange, Aurantium orange and lemon).         After and filtration these samples, the concentration of sodium and potassium was estimated by the Flame Photometer. The results of this study showed that the concentration of potassium was high in these samples compared to the concentration of sodium. The values of concentration of potassium in orange and lemon varieties ranged from 80 ppm of aurantium orange to higher than 250 ppm of navel and blood orange. While the concentration of sodium values ranged from 5 ppm for sour orange and 36 ppm for navel orange. This study also included estimating the sugar in the orange and lemon samples by Refract meter. The values obtained were found to be close to 13.44 for lemon and 13.53 for mandarin orange.
Keywords: Mineral Salts; Orange; Lemon; Flame Photometer